The Specificity of Inhibitory Impairments in Autism and Their Relation to ADHD-Type Symptoms. - Sanderson, Charlotte; Allen, Melissa (Journal of Autism & Developmental Disorders, 2013)
Findings on inhibitory control in autism have been inconsistent. This is perhaps a reflection of the different tasks that have been used. Children with autism (CWA) and typically developing controls, matched for verbal and non-verbal mental age, completed three tasks of inhibition, each representing different inhibitory subcomponents: Go/No-Go (delay inhibition), Dog-Pig Stroop (conflict inhibition), and a Flanker task (resistance to distractor inhibition). Behavioural ratings of inattention and hyperactivity/impulsivity were also obtained, as a possible source of heterogeneity in inhibitory ability. CWA were only impaired on the conflict inhibition task, suggesting that inhibitory difficulty is not a core executive deficit in autism. Symptoms of inattention were related to conflict task performance, and thus may be an important predictor of inhibitory heterogeneity.